America's Prescient Dissenters: Senator J. William Fulbright and Dr. Andrew J. Bacevich's Principled Dissent of US Policy in Vietnam and Iraq and their Enduring Perspectives. Issue 3 (2nd October 2017) - LeVien, Douglas A.
ABSTRACT: During the Cold War, the spread and fear of communism furnished the overarching ideological rationale for American foreign policy and for the deployment of United States military forces and resources. Subscribing to the domino theory and its potential impact on Southeast Asia, the Johnson Administration committed the United States to the Vietnam War. Following the September 11, 2001 attacks on the United States, and the commencement of the Global War on Terrorism, Washington once again set a national agenda rooted in a simplistic analysis reminiscent of Vietnam and the domino theory. Ignorant of Iraq's mammoth sectarian, historical, ethnic, and global strategic complexities, the Bush Administration launched Operation Iraqi Freedom (OIF). The absence of critical analysis, contrarian viewpoints, and sound judgment characterized the US policy and strategy for both the Vietnam War and OIF, exhibiting the lack of moral courage that the national security enterprise seeks, but seldom attains. Faced with this challenge, this article draws attention to the ethical lessons we can learn from the dissent of William Fulbright and Andrew Bacevich.